2006
DOI: 10.1007/s10495-006-0011-2
|View full text |Cite
|
Sign up to set email alerts
|

Roles of survivin isoforms in the chemopreventive actions of NSAIDS on colon cancer cells

Abstract: NSAIDs downregulate survivin (an apoptosis inhibitor), increase apoptosis and reduce growth of colon polyps and cancers. Recently, anti- and pro-apoptosis isoforms of survivin were identified. The roles of these isoforms in NSAID-induced colon cancer cell death have not been examined, and is the focus of this study. The anti-apoptosis isoforms, wild-type (WT) survivin and survivin-DeltaEx3, and the pro-apoptosis isoform, survivin-2b, were present in HT-29 and RKO cells. Indomethacin treatment significantly dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…It reduces proliferation rates of HT-29 colon cancer cells (Kapitanović et al 2006). It also induces apoptosis by up-regulating pro-apoptotic genes and down-regulating anti-apoptotic genes and is therefore associated with potent inhibitory action on colon cancer growth (Mandayam et al 2007). However, the multiple dosing oral conventional formulation of indomethacin will result in systemic accumulation of the drug, leading to untoward side effects and adverse reactions (Marsh et al 1986).…”
Section: Introductionmentioning
confidence: 99%
“…It reduces proliferation rates of HT-29 colon cancer cells (Kapitanović et al 2006). It also induces apoptosis by up-regulating pro-apoptotic genes and down-regulating anti-apoptotic genes and is therefore associated with potent inhibitory action on colon cancer growth (Mandayam et al 2007). However, the multiple dosing oral conventional formulation of indomethacin will result in systemic accumulation of the drug, leading to untoward side effects and adverse reactions (Marsh et al 1986).…”
Section: Introductionmentioning
confidence: 99%
“…These results showed that inhibition of autophagy by 3-MA and Atg7 siRNA had significant effects on the half-life of the apoptosis inhibitor survivin under certain conditions. We previously determined that regulation of survivin levels by NSAIDs is a key factor for apoptosis induction in colon cancer cells [24]. survivin also regulates autophagy [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported to cause growth inhibition, induction of apoptosis, and reduction in proliferation rates of HT-29 colon cancer cells (5). It has been established recently that indomethacin down-regulates survivin (an apoptosis inhibitor) in the case of colon cancer, thereby causing apoptosis and cancer cell death (6). Indomethacin is also reported to decrease EP2 prostanoid receptor expression in colon cancer cells (7).…”
Section: Introductionmentioning
confidence: 99%